1984
DOI: 10.1128/jb.160.3.966-970.1984
|View full text |Cite
|
Sign up to set email alerts
|

Defective plasma membrane assembly in yeast secretory mutants

Abstract: Yeast mutants that are conditionally blocked at distinctive steps in secretion and export of cell surface proteins have been used to monitor assembly of integral plasma membrane proteins. Mutants blocked in transport from the endoplasmic reticulum (secl8), from the Golgi body (sec7 and secl4), and in transport of secretory vesicles (secl) show dramatically reduced assembly of galactose and arginine permease activities. Simultaneous induction of galactose permease and oa-galactosidase (a secreted glycoprotein) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…These high mol. wt proteins appeared with kinetics reflecting the slow recovery of secl8 cells from the heat induced secretion block (Tschopp et al, 1984). This experiment, however, is not a true pulse-chase experiment.…”
Section: Resultsmentioning
confidence: 79%
“…These high mol. wt proteins appeared with kinetics reflecting the slow recovery of secl8 cells from the heat induced secretion block (Tschopp et al, 1984). This experiment, however, is not a true pulse-chase experiment.…”
Section: Resultsmentioning
confidence: 79%
“…An explanation for two populations of post-Golgi vesicles is that one population, transporting materials for plasma membrane and cell-wall synthesis, such as the major plasma membrane ATPase, Pmalp, and the cell-wall component, Bgl2p, is specifically targeted to regions of active growth, while another population, carrying periplas-mic enzymes and proteins secreted into the medium (invertase, acid phosphatase, Exglp), does not need to be targeted so precisely. This model predicts that other secreted proteins shown to accumulate in sec mutants but not directly involved in surface expansion, such as the periplasmic enzyme o~-galactosidase (Tschopp et al, 1984) and several plasma membrane permeases (sulfate, galactose, and arginine permease [Novick et al, 1980;Tschopp et al, 1984]) should be present in the invertase-containing vesicles but not in vesicles transporting Bgl2p.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the transport of Ath1p to vacuoles via the secretory pathway as proposed from previous works [101,104] is doubtful since the amino acid sequence of this protein does not present any signal sequence and consensus cleavage sites characteristic of proteins following this pathway [8]. It is therefore suggested that the acid trehalase can be secreted to the periplasm similarly to the externalization of some permeases and H -ATPase [114,115]. The acid trehalase and extracellular trehalose will then be internalized from the surface and delivered to the vacuoles by endocytosis.…”
Section: Hydrolysis By Neutral (Nth1p Nth2p) and Acid (Ath1p) Trehalmentioning
confidence: 96%